Plastic Impacts in Argentina: a Critical Research Review Contributing to the Global Knowledge - Ronda, Ana Carolina (2021)
Purpose of review: Plastic pollution research has experienced exponential growth in the last decade; however, Argentina concentrates more than 70% of their research in the last 4 years. This review compiles regional research on plastic pollution in water, soil, sediment, air and organisms in Argentina. It discusses current sampling, quantification, and plastics identification methodologies while analyzing levels, gaps, and opportunities. Recent findings: Research in plastic pollution was mainly focused on the biosphere component (52.9%), followed by the hydrosphere component (29.4%), and finally the lithosphere component (17.7%), with less than 20% addressing multiple components simultaneously. Sixty percent of this research was focused around microplastics, and less than 20% have considered multiple plastic debris sizes. Marine coastal species from Argentina had higher levels of microplastics than organisms from other South American studies, while microfibers were identified in 100% of the freshwater organisms studied. The lowest microplastic concentrations were found in lakes and in the Paraná and La Plata rivers, while the maximum concentrations were found in Pampa´s streams. There was a lack of standardization in methodology and unit expression in studies of sediment microplastics, which hinders comparison between reports. Summary: Argentine scientists have created the national alliance called SciEnce for Plastic Impacts Argentina (SEPIA). SEPIA is a network which aims to systemize plastic pollution research, coordinate methodologies, and enhance relationships with decision-makers, NGOs, and the general public. A time gap was found between the designation of principal international multilateral agreements and the implementation of national regulations for plastic waste treatment, with a tendency to include advanced concepts as Extended Producer Responsibility and Circular Economy.